2016
DOI: 10.1111/dme.13277
|View full text |Cite
|
Sign up to set email alerts
|

RD Lawrence Lecture 2015 Old habits are hard to break: lessons from the study of hypoglycaemia

Abstract: Despite the introduction of newer technologies and improved insulin formulations, recurrent hypoglycaemia continues to affect the lives of many people with Type 1 and Type 2 diabetes. Developing strategies or therapies designed to prevent or minimize hypoglycaemia risk is of utmost importance to help individuals safely achieve glycaemic targets. Novel, educational or behavioural approaches need to be based on a clear understanding of the mechanisms underpinning both the detection of hypoglycaemia and why repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Likewise, recovery of CRR through hypoglycaemia avoidance [47] is in keeping with the second characteristic of habituation; namely, 'if the stimulus [hypoglycaemia] is withheld, the response [CRR] tends to recover over time (spontaneous recovery)'. In fact, studies in rodent and human models of IAH have reported findings consistent with six of the nine principles of habituation proposed by Thompson and Spencer (for review see [48]). …”
Section: Habituation and Impaired Hypoglycaemia Awarenessmentioning
confidence: 71%
“…Likewise, recovery of CRR through hypoglycaemia avoidance [47] is in keeping with the second characteristic of habituation; namely, 'if the stimulus [hypoglycaemia] is withheld, the response [CRR] tends to recover over time (spontaneous recovery)'. In fact, studies in rodent and human models of IAH have reported findings consistent with six of the nine principles of habituation proposed by Thompson and Spencer (for review see [48]). …”
Section: Habituation and Impaired Hypoglycaemia Awarenessmentioning
confidence: 71%
“…IAH is not an “all or none phenomenon” but reflects a continuum in which differing degrees of impaired awareness can occur and can vary over time in any one individual. IAH is proposed to be a result of intracellular and extracellular physiological adaptations to recurrent hypoglycemia that are in essence survival responses designed to protect the cell from subsequent exposure to glucose deprivation . This adaptive process is referred to as habituation .…”
Section: Hypoglycemia Awarenessmentioning
confidence: 99%
“…IAH is proposed to be a result of intracellular and extracellular physiological adaptations to recurrent hypoglycemia that are in essence survival responses designed to protect the cell from subsequent exposure to glucose deprivation. 112 This adaptive process is referred to as habituation. 113 A habituated response can also be, at least temporarily, reversed by the introduction of a novel (heterotypic) stimulus (dishabituation).…”
Section: Hypoglycemia Awarenessmentioning
confidence: 99%
“…Hypoglycemia is the main hurdle for achieving optimal glycemic control in patients on insulin therapy [ 3 ]. Development of strategies or therapies to control hypoglycemia is important to help individuals achieve glycemic targets [ 4 ]. Achieving optimum glycemic control following the diagnosis of T2DM is vital to improving clinical outcomes, yet many patients and clinicians are hesitant to initiate and intensify insulin therapy.…”
Section: Introductionmentioning
confidence: 99%